2015
DOI: 10.1016/j.bbr.2014.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Reduced processing of alcohol cues predicts abstinence in recently detoxified alcoholic patients in a three-month follow up period: An ERP study

Abstract: One of the major challenges in alcohol dependence is relapse prevention, as rates of relapse following detoxification are high. Drug-related motivational processes may represent key mechanisms in alcoholic relapse. In the present study, event-related potentials (ERPs) were recorded during a visual oddball task administered to 29 controls (11 females) and 39 patients (9 females). Deviant stimuli were related or unrelated to alcohol. For patients, the task was administered following a 3-week detoxification cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 91 publications
6
40
0
Order By: Relevance
“…Similar findings were reported for animal models of alcohol addiction (Criado and Ehlers 2009;Ehlers et al 2014;Slawecki et al 2003). The P3 component is therefore considered the best predictor and biomarker for the relapse risk after alcohol withdrawal (Petit et al 2015). In addition, the P3 has been suggested as a potential marker for vulnerability to develop AUD.…”
Section: P3supporting
confidence: 77%
“…Similar findings were reported for animal models of alcohol addiction (Criado and Ehlers 2009;Ehlers et al 2014;Slawecki et al 2003). The P3 component is therefore considered the best predictor and biomarker for the relapse risk after alcohol withdrawal (Petit et al 2015). In addition, the P3 has been suggested as a potential marker for vulnerability to develop AUD.…”
Section: P3supporting
confidence: 77%
“…A high WM capacity has also been linked to a high ability of directing attention toward goal-relevant information and of ignoring distractions, i.e., attentional control [ 76 78 ]. Chronic alcohol abusers often exhibit excessive attentional focus on alcohol-related cues [ 79 ] that could increase the risk of relapse [ 79 81 ]. Effective attentional control is hence essential to overcome these attentional biases and to maintain abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, the P3 of the event-related potentials (ERPs) related to the involvement of motivational and arousal systems (Petit et al, 2015) and the Slow Positive Waves (SPWs) of the ERPs which reflect the brain’s activation of motivational systems to emotional cues (Cuthbert et al, 2000) were most suggested. It is indicated that both P3 and SPW amplitudes in response to smoking cues are significantly more enhanced in smokers than in the healthy at frontal and central sites indicating that smokers show more attention bias for smoking cues (Namkoong et al, 2004; Littel and Franken, 2007; Marianne et al, 2012).…”
Section: Cue Reactivity In Nicotine and Alcohol Addictionmentioning
confidence: 99%